2019
DOI: 10.1111/hsc.12892
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of healthcare professionals in providing care to South Asian ethnic minority patients in Hong Kong: A qualitative study

Abstract: Ethnic minorities across the globe encounter disparities in healthcare. While a great deal of research has been conducted on the experiences of these patients, studies focusing on the perspectives of healthcare professionals are limited, particularly in the context of Asia. This study explores the perceptions of and challenges faced by Hong Kong healthcare professionals in the provision of culturally appropriate care to South Asian ethnic minority patients. Taking a qualitative approach, interviews were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…The age of participants ranged from 24 to 89 years old. The included studies were conducted in 6 different countries: 15 in the United States [ 8 , 26 – 39 ], 3 in the United Kingdom [ 40 42 ], 2 in Australia [ 43 , 44 ], 1 in Canada [ 45 ], Spain [ 46 ] and Hong Kong [ 47 ] respectively. 11 studies reported findings from the African American community, 2 each from the Pakistani, Indigenous Australian and South Asian communities and 1 each from the African Caribbean, Latin American, Native American, Roma and Iranian communities.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The age of participants ranged from 24 to 89 years old. The included studies were conducted in 6 different countries: 15 in the United States [ 8 , 26 – 39 ], 3 in the United Kingdom [ 40 42 ], 2 in Australia [ 43 , 44 ], 1 in Canada [ 45 ], Spain [ 46 ] and Hong Kong [ 47 ] respectively. 11 studies reported findings from the African American community, 2 each from the Pakistani, Indigenous Australian and South Asian communities and 1 each from the African Caribbean, Latin American, Native American, Roma and Iranian communities.…”
Section: Resultsmentioning
confidence: 99%
“…Minority patients reported that healthcare providers ignored or rushed them during their clinical interactions [ 32 , 40 , 41 , 44 , 47 ]. Some patients further stated that they received less priority and were unfairly skipped over by patients of perceived privileged races [ 29 , 31 , 32 , 34 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations